2008
DOI: 10.1124/mol.108.045336
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H2 Receptor Trafficking: Role of Arrestin, Dynamin, and Clathrin in Histamine H2 Receptor Internalization

Abstract: Agonist-induced internalization of G protein-coupled receptors (GPCRs) has been implicated in receptor desensitization, resensitization, and down-regulation. In the present study, we sought to establish whether the histamine H2 receptor (H2r) agonist amthamine, besides promoting receptor desensitization, induced H2r internalization. We further studied the mechanisms involved and its potential role in receptor resensitization. In COS7 transfected cells, amthamine induced H2r time-dependent internalization, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
3
19
0
2
Order By: Relevance
“…As the crossdesensitization was independent not only of second messengers but also of downstream second messenger-dependent protein kinases, a possible cross-regulation at the receptor level was evaluated. In a previous study performed in U937 cells endogenously expressing H2R as well as in COS7 and HEK293T cells transiently expressing H2R, we reported that the receptor is internalized following histamine or H2R-agonist stimulation as part of receptor trafficking (Fernandez et al, 2008). Furthermore, H1R is also internalized following histamine stimulation in H1R stably transfected CHO-K1 cells (Self et al, 2005;Hishinuma et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the crossdesensitization was independent not only of second messengers but also of downstream second messenger-dependent protein kinases, a possible cross-regulation at the receptor level was evaluated. In a previous study performed in U937 cells endogenously expressing H2R as well as in COS7 and HEK293T cells transiently expressing H2R, we reported that the receptor is internalized following histamine or H2R-agonist stimulation as part of receptor trafficking (Fernandez et al, 2008). Furthermore, H1R is also internalized following histamine stimulation in H1R stably transfected CHO-K1 cells (Self et al, 2005;Hishinuma et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to determine whether a direct cause-effect existed between receptor cointernalization and crossdesensitization we used U937 derived clones (DC6, A2, and GB4) previously characterized in our laboratory that exhibit blockade of H2R internalization by different mechanisms. DC6 cell line was obtained by stable transfection with a dynamin dominant negative mutant which proved to dampen agonist-induced H2R endocytosis (Fernandez et al, 2008). A2 cells have a GRK2 antisense construct that diminishes GRK2 expression levels at ASPET Journals on May 12, 2018 molpharm.aspetjournals.org and diminishes both H2R desensitization and internalization (Fernandez et al, 2002(Fernandez et al, , 2011.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the GTPase dynamin has been identified as a binding partner for the H 2 receptor, both in vitro and in vivo (Xu et al, 2008). A role of dynamin, b-arrestin, and clathrin in H 2 receptor 614 internalization has indeed also been reported (Fernandez et al, 2008).…”
Section: B Signal Transduction Mechanismsmentioning
confidence: 99%
“…Desensitization of the H 2 receptor is suggested to involve both GPCR kinase 2 and 3 (Rodriguez-Pena et al, 2000;Fernandez et al, 2011). The C-terminal tail is required for membrane targeting through a putative palmitoylation-mediated mechanism (Fukushima et al, 1997), and the last 51 amino acids are reported to be crucial for internalization (Fernandez et al, 2008). Recently, the GTPase dynamin has been identified as a binding partner for the H 2 receptor, both in vitro and in vivo (Xu et al, 2008).…”
Section: B Signal Transduction Mechanismsmentioning
confidence: 99%